Preparation method and application of citronellol-based diol related polyester

By using polyester materials prepared by biobased raw materials such as citronellol and dopamine hydrochloride, the problem of low bond strength of existing adhesives in wet environments is solved, and a biomass polyester with high viscosity and thermal stability is achieved, which is suitable for underwater adhesion agents.

CN119529253APending Publication Date: 2025-02-28WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311084239.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing adhesives have low bonding strength in wet environments and poor water resistance, making it difficult to meet the bonding needs in underwater or humid environments.

Method used

A new diol monomer and dibasic acid monomer were prepared by halogenation reaction and hydroxyethylation of phenolic hydroxyl groups. Then, a polyester material with a rigid structure and a flexible chain structure was synthesized by melt polymerization, and a cross-linked copolymer was reacted with dopamine hydrochloride.

Benefits of technology

The prepared biomass polyester has high viscosity, thermal stability and excellent wet adhesion properties. It is suitable for underwater adhesion agents, significantly improving the adhesion strength in wet environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_3
    Figure QLYQS_3
  • Figure QLYQS_4
    Figure QLYQS_4
Patent Text Reader

Abstract

The invention discloses citronellol-based biomass polyester as well as a preparation method and application thereof, and the method comprises the following steps: carrying out double-bond addition on citronellol, and carrying out hydroxylation treatment on citronellol to obtain a biomass dihydric alcohol monomer M1; 1-hydroxy-3, 4-dimethoxybenzoic acid and chloroacetic acid ether are subjected to coupling, and a biomass binary acid monomer M2 is obtained; and reacting the biomass dihydric alcohol M1 with the biomass dibasic acid M2, reacting with dopamine hydrochloride, and refining to obtain the citronellol-based biomass polyester. The polyester has the characteristics of excellent wet adhesive strength, stable performance, no pollution and the like, can be used for underwater building repair and underwater adhesives, and improves the adsorption capacity in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer synthesis, and in particular relates to a preparation method based on citronellol-based diol monomers and homopolyesters and copolyesters thereof. The prepared biomass polyester can be used as a biological underwater adhesive. Background Art

[0002] In daily life, adhesives require a clean surface to ensure successful bonding. In some special industries, water operations are often required, or even direct bonding under water. With the increasing number of water conservancy construction, underwater building maintenance and other projects, there is an urgent need for a special adhesive with excellent adhesion performance under water or other wet environments. In recent years, wet adhesion has received widespread attention, and various underwater adhesives have been developed. Xie et al. mixed poly 1-vinyl imidazole (PVI) and gelatin solution and added Fe 3+ The hydrogel adhesive was prepared for use as a wound healing dressing and can be sprayed with Zn 2+ Solution to facilitate replacement of adhesive auxiliary materials, Zn 2+ The addition of zincions can improve the cohesion of the adhesive while reducing the adhesion, and the damage to the wound is small when changing the auxiliary material [1] XieT, Ding J, Han X, et al. Wound dressing change facilitated by spraying zincions [J]. Materials Horizons, 2020, 7 (2): 605-614. Commercial adhesives are generally designed for use in dry environments and have poor water resistance. For example, polyacrylamide is easily corroded by water in a wet environment, and the corrosion damage has a significant impact. The viscosity will significantly reduce its performance due to water absorption. Another issue that needs to be considered is that in a wet environment, the wet viscosity strength is an indicator of its performance. How to improve its wet viscosity strength is also a difficult problem. For bonding technology, achieving high bonding strength and long-term stability in a wet environment is a huge challenge. In order to obtain high wet adhesion performance, researchers have made many attempts. It is believed that the poor wet adhesion performance of adhesives is mainly due to the presence of water film, but it is difficult to remove water molecules on the surface of the substrate. Underwater or in other humid environments, water molecules on the surface of the adhesive substrate will form a water film, which will hinder the adhesive from fully contacting and penetrating the substrate surface. The water molecules remaining in the gaps of the adhesive interface will also have a negative effect on the subsequent work of the adhesive. Therefore, there are very few adhesives with high wet bonding strength.

[0003] With the advancement of science and technology, the awareness of green environmental protection and sustainable development has increased, and the development of new renewable resources and how to use biomaterials to prepare adhesives to reduce dependence on petroleum raw materials are current research hotspots. Compared with petroleum-based adhesives, bio-based adhesives are renewable, biodegradable and have good compatibility. However, the currently synthesized bio-based adhesives have poor wet adhesion properties, and the application of bio-based adhesives is limited. In addition, water has a variety of corrosive effects on adhesives. Bio-based adhesives have better environmental compatibility, but are more affected by water. To solve the above problems, this paper introduces a large number of catechol groups into the adhesive. [2][3] [2] Jia Z, Zeng Y, Tang P, et al. Conductive, tough, transparent, and self-healing hydrogels based on catechol–metal ion dual self-catalysis[J].Chemistry of Materials, 2019, 31 (15): 5625-5632. [3] Guo Q, Chen J, Wang J,et al. Recent progress in synthesis and application of mussel-inspiredadhesives[J]. Nanoscale, 2020, 12 (3): 1307-1324. It can improve the water resistance of the adhesive and break the water film to increase the effective contact area between the adhesive and the substrate, so as to achieve enhanced adhesive strength and wet adhesive strength. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention uses bio-based renewable chemicals such as citronellol derived from natural essential oils as raw materials, adopts halogenation reaction and hydroxyethylation of phenolic hydroxyl groups to prepare new diol monomers M1 and dibasic acid monomers M2, and then uses melt polymerization to synthesize new polyester materials with good rigid structure and flexible chain structure, and uses a one-pot method to react polyester P with dopamine hydrochloride to form a cross-linked copolymer. Dopamine hydrochloride [4] [4] Yu Xi. Preparation and application of bio-based polyester underwater adhesive [D]. Jiangnan University, 2021. DOI: 10.27169 / d.cnki.gwqgu.2021.001625. It has a catechol group, which makes its product have excellent adhesion and excellent wet adhesion performance. The polyester material prepared by the present invention has strong viscosity and high thermal stability, which makes it have good development prospects as an underwater adhesive in the fields of underwater construction and maintenance.

[0005] The present invention adopts the following technical solutions.

[0006] A biomass polyester P based on citronellol, characterized in that: the structural formula is shown below.

[0007] (1) Synthesis of monomers.

[0008] Synthesis of a diol M1: At room temperature, citronellol with CAS number 68916-43-8 is and hydrogen chloride in a certain proportion into a reaction vessel, stir to dissolve, then add an appropriate amount of Pd / CaCO3 solid particles, then heat the reaction mixture to 65-70°C, continue stirring to react for 2-4 hours, and then cool to room temperature. After filtering, add 0.10 mol / L sodium hydroxide solution while stirring until the solution color does not change significantly, filter, extract the filtrate with carbon tetrachloride, take the lower layer of liquid after standing for a period of time, and then distill at a temperature of about 85-90°C. The remaining liquid is the desired diol monomer, and the structure is shown in Formula 2: .

[0009] Synthesis of a dibasic acid M2.

[0010] Under low pressure, a certain proportion of 2-hydroxy-3,4-dimethoxybenzoic acid (CAS No. 5653-46-3) and chloroacetic acid are placed in a reactor, acetonitrile is added under stirring until the reactant is dissolved, and then 0.10 mol / L sodium hydroxide solution is added thereto, and the ratio of 0.10 mol / L sodium hydroxide solution to chloroacetic acid is 1:1.1-1.2. Then, the reaction mixture is stirred and heated to 75-82°C. After reacting for 2-5 hours, the heating is stopped, and then cold water is added to the reaction mixture until the insoluble matter no longer increases. The reaction mixture is filtered, and the filter residue is washed with cold distilled water, filtered again, and the filter residue is dried in an oven at 60°C for 2-3 hours to obtain a dibasic acid monomer M2, the structure of which is shown in Formula 3: .

[0011] The air in the reactor is replaced with nitrogen. Under nitrogen protection, the diol monomer M1, dibasic acid monomer M2 and condensation catalyst prepared in (1) are added into the reaction container in a certain proportion, and the reaction is stirred at 150-170°C for 5-6 hours. The vacuum degree of the reaction system is then controlled at 50-100 Pa. The reaction mixture is heated to 210-230°C within 1 hour. After the stirring reaction is continued for 3-4 hours, the reaction mixture is cooled to room temperature under a nitrogen atmosphere. Chloroform is then added to the reaction mixture until it is dissolved. The mixture is filtered. A sufficient amount of methanol is added to the filtrate until the amount of precipitation no longer increases. The filtrate is filtered. The filter residue is washed 3 times with cold methanol, filtered again, and then dried in an oven at 70-80°C for 2-3 hours to obtain a citronellol-based biomass polyester P.

[0012] 3. A preparation method of a biomass polyester P based on citronellol, characterized in that: in step (1), the molar ratio of citronellol to hydrogen chloride is 1:(1.0-2.0); the molar ratio of 2-hydroxy-3,4-dimethoxybenzoic acid to chloroacetic acid is 1:(1.3-1.7).

[0013] 4. A preparation method for a biomass polyester P based on citronellol, characterized in that: the polycondensation catalyst in step (2) is a composite catalyst consisting of one, two or three of germanium dioxide, cerium dioxide and aluminum triethoxide, and the amount of the polycondensation catalyst is 0.01% to 0.05% of the mass of the dibasic acid monomer M2.

[0014] 5. A preparation method of a biomass polyester P based on citronellol, characterized in that: in step (2), the molar ratio of the diol monomer M1 to the dibasic acid monomer M2 is 1:(1.0-1.2).

[0015] The use of the polyester P obtained by a preparation method of a citronellol-based biomass polyester P is characterized by being used as an underwater adhesive. The preparation method of the adhesive is as follows: a citronellol-based biomass polyester P is reacted with a hydrochloric acid dopamine monomer at a mass ratio of 100: (80-85), and then an appropriate amount of DMSO is added, and the mixture is stirred and mixed evenly, an inhibitor (4-methoxy-benzaldehyde) is added to prevent free radical polymerization, argon gas is introduced for bubbling, air in the liquid is removed, and the reaction is carried out at 65°C for 2.5 hours. The product is centrifuged at high speed, a precipitant is added after standing, impurities and monomer residues are removed, and the filter residue is filtered and placed in a 60°C oven to dry for 2-3 hours to obtain the target product.

[0016] Beneficial effects.

[0017] 1. Using renewable green chemicals such as citronellol and dopamine hydrochloride to replace petroleum-based monomers as the basic raw materials for preparing polyester can replace traditional petroleum adhesives and alleviate the problem of oil resource shortage to a certain extent.

[0018] 2. Bio-based adhesives not only have good biocompatibility, but also have good biodegradability, reducing harmful effects on the human body or the biological environment.

[0019] 3. The present invention also provides a new polyester monomer, which provides a new idea for the preparation of polyester. The prepared polyester is rich in catechol groups, which makes it better at absorbing water molecules at the adhesion interface and reducing the barrier effect of the water film to improve the wet adhesion performance of the adhesive. It effectively solves the problems of traditional adhesives such as acrylic acid, methacrylic acid, and acrylates that cannot remove biological toxicity and have low underwater adhesion coefficients, and meets the existing market requirements for biomedical and underwater adhesives.

[0020] 4. The high-viscosity bio-polyester prepared by the present invention uses an efficient catalyst and an efficient condensation reaction to prepare a high-molecular-weight bio-based polyester with greatly improved viscosity, which solves the problems of common adhesives having biological toxicity and poor performance in a humid environment, and can be widely used in biomedicine, underwater adhesives and other fields.

[0021] Specific implementation methods.

[0022] The present invention is not limited by the following examples, and we will further illustrate by examples. It is worth noting that the raw materials involved in the present invention are all conventional commercial products. In order to more clearly understand the purpose, technical solutions and advantages of the present invention, we will further describe the present invention in detail with reference to examples. It should be pointed out that the data involved in the specific examples described below are only used to explain the present invention and are not limited to the scope of the present invention.

[0023] The monomers and polyesters prepared in the examples were determined by using a Bruker Avance DMX600 nuclear magnetic resonance instrument and a VERTEX 70 Fourier transform infrared spectrometer from Bruker Spectroscopy Instruments of Germany; the adhesive performance test was performed by connecting the substrates with an adhesive using a lap-cut method, and the shear bonding strength was tested using a Z005 universal material testing machine from Zwick Company of Germany, in accordance with ISO 6892-1 standard; the molecular weight and its distribution were determined by dissolving the polymer product in tetrahydrofuran and measuring it using a water 2412 gel chromatograph.

[0024] Water absorption performance test.

[0025] Place the sample in a constant temperature and humidity oven, record the mass before and after and calculate the water absorption; the result is the average of three test samples.

[0026] Yield = 100% × actual production of target product / theoretical production of target product.

[0027] Example 1.

[0028] Synthesis of a diol monomer M1: 6.25 g (0.04 mol) of citronellol and 0.05 mol of hydrogen chloride water are added to a reaction container in proportion, stirred to mix evenly, then 0.12 g of Pd / CaCO3 solid particles are added, and then the reaction mixture is heated to 65°C, stirred and reacted for 4 hours, and then cooled to room temperature. After filtering, 0.10 mol / L sodium hydroxide solution is added thereto while stirring until the color of the solution does not change significantly, filtered, and the filtrate is extracted with carbon tetrachloride, and then the temperature is set at 90°C in a rotary evaporator, and distilled for 3 hours. The remaining liquid is the target product M1, and the yield is 84.3%.

[0029] Example 2.

[0030] Synthesis of a dibasic acid monomer M2: 7.92 g of 2-hydroxy-3,4-dimethoxybenzoic acid and 5.67 g of chloroacetic acid are placed in a reactor, and sufficient acetonitrile is added under stirring until the reactants are completely dissolved, and then 400 ml of 0.10 mol / L sodium hydroxide solution is added thereto, and the mixture is stirred and mixed evenly, and then vacuumed. The mixture is heated to 80°C, reacted for 5 hours, and then heating is stopped. Cold water is then added to the reaction mixture until the insoluble matter no longer increases, and the mixture is filtered. The filter residue is washed with cold distilled water, filtered again, and the filter residue is dried in an oven at 60°C for 2 to 3 hours to obtain a dibasic acid monomer M2 with a yield of 86.4%.

[0031] Example 3.

[0032] The air in the reactor was replaced with nitrogen. Under the protection of nitrogen, 5.22 g of the prepared diol monomer M1, 8.10 g of the dibasic acid monomer M2, and 0.81 g of the polycondensation catalyst TiCl3 / LiCl were added into the reaction container, stirred and reacted at 70°C for 5 hours, and then the vacuum degree of the reaction system was controlled at 80 Pa. The reaction mixture was heated to 210°C within 1 hour, and the stirring reaction was continued for 4 hours. The reaction mixture was cooled to room temperature under a nitrogen atmosphere, and then chloroform was added to the reaction mixture until it was dissolved, filtered, and sufficient methanol was added to the filtrate until the precipitation no longer increased. Filter, wash the obtained filter residue with cold methanol 3 times, filter again, and then dry it in an oven at 70-80°C for 2-3 hours to obtain a citronellol-based biomass polyester P with a number average molecular weight of 34587 g / mol and a yield of 83.2%.

[0033] Example 4.

[0034] 9.80g of biomass polyester P was reacted with 7.84g of dopamine hydrochloride monomer, and then sufficient DMSO was added to stir and mix evenly and completely dissolve, 0.1g of inhibitor (4-methoxy-benzaldehyde) was added to prevent free radical polymerization, argon was introduced for 15 minutes to remove the air in the liquid, and the reaction was carried out at 65°C for 2.5 hours. The product was centrifuged at high speed, and a precipitant (8-hydroxyquinoline) was added after standing to remove impurities and monomer residues, filtered and washed with propanol three times, and then the filter residue was placed in a 60°C oven and dried for 3 hours to obtain the target product P1, with a number average molecular weight of 43531g / mol and a yield of 86.7%.

[0035] Example 5.

[0036] 9.80g of biomass polyester P was reacted with 8.33g of dopamine hydrochloride monomer, and then enough DMSO was added to stir and mix evenly and completely dissolve, 0.1g of inhibitor (4-methoxy-benzaldehyde) was added to prevent free radical polymerization, argon was introduced for 15 minutes to remove the air in the liquid, and the reaction was carried out at 65°C for 2.5 hours. The product was centrifuged at high speed, and a precipitant (8-hydroxyquinoline) was added after standing to remove impurities and monomer residues, filtered and washed with propanol 3 times, and then the filter residue was placed in a 60°C oven and dried for 3 hours to obtain the target product P2, with a number average molecular weight of 43497g / mol and a yield of 87.2%.

[0037] Example 6.

[0038] 4.90g of biomass polyester P was reacted with 4.17g of dopamine hydrochloride monomer, and then enough DMSO was added to stir and mix evenly and completely dissolve, 0.1g of inhibitor (2,2-diphenyl-1-trinitrobenzene) was added to prevent free radical polymerization, argon was introduced for 15 minutes to remove the air in the liquid, and the reaction was carried out at 65°C for 2.5 hours. The product was centrifuged at high speed, and after standing, a precipitant (8-hydroxyquinoline) was added to remove impurities and monomer residues, filtered and washed with propanol three times, and then the filter residue was placed in a 60°C oven and dried for 3 hours to obtain the target product P3, with a number average molecular weight of 38957g / mol and a yield of 83.2%.

[0039] Example 7.

[0040] 7.35g of biomass polyester P was reacted with 6.23g of dopamine hydrochloride monomer, and then enough DMSO was added to stir and mix evenly and completely dissolve, 0.1g of inhibitor (4-methoxy-benzaldehyde) was added to prevent free radical polymerization, argon was introduced for 15 minutes to remove the air in the liquid, and the reaction was carried out at 65°C for 3 hours. The product was centrifuged at high speed, and a precipitant (8-hydroxyquinoline) was added after standing to remove impurities and monomer residues, filtered and washed with propanol 3 times, and then the filter residue was placed in a 60°C oven and dried for 3 hours to obtain the target product P4, with a number average molecular weight of 45872g / mol and a yield of 86.2%.

[0041] Example 8.

[0042] 6.13g of biomass polyester P was reacted with 5.21g of dopamine hydrochloride monomer, and then enough DMSO was added to stir and mix evenly and completely dissolve, 0.1g of inhibitor (4-methoxy-benzaldehyde) was added to prevent free radical polymerization, argon was introduced for 15 minutes to remove the air in the liquid, and the reaction was carried out at 70°C for 3 hours. The product was centrifuged at high speed, and a precipitant (8-hydroxyquinoline) was added after standing to remove impurities and monomer residues, filtered and washed with propanol 3 times, and then the filter residue was placed in a 60°C oven and dried for 3 hours to obtain the target product P5, with a number average molecular weight of 46873g / mol and a yield of 88.2%.

[0043] .

[0044] [5] Pu Yefen. Analysis and modification of bonding performance of S36 hot melt adhesive for book binding[J]. Adhesion, 2023, 50(4): 29-32. DOI: 10.3969 / j.issn.1001-5922.2023.04.008.

[0045] Note: Mn and Mn1 are the number average molecular weight before degradation and after being placed in PBS buffer for one year, respectively.

[0046] From the above embodiments and related data, it can be seen that the polyester synthesized by using citronellol and 2-hydroxy-3,4-dimethoxybenzoic acid as the main raw materials of the present invention greatly improves the adhesive strength in a wet environment compared with sodium silicate, and the adhesive strength under dry conditions is further enhanced. Among them, 4-methoxy-benzaldehyde is selected as the suppressor under the same ratio conditions, and the prepared polyester has better performance than 2,2-diphenyl-1-trinitrobenzene. The best reaction time is 3 hours, the temperature is 70°C, and the mass ratio is 100:85. The adhesive strength is 4.1Mpa and the wet adhesive strength is 3.2Mpa. Due to the addition of dopamine hydrochloride, the wet adhesive strength of the polyester is significantly improved. Similarly, since dopamine hydrochloride is also a bio-based material, the degradability of the polyester is further improved and the biological toxicity is reduced.

[0047] In summary, the synthesis of existing adhesive materials still mainly uses petroleum-based raw materials, and requires the use of more catalysts, the catalytic efficiency is low, and the obtained products also have performance defects, which makes it difficult to meet the requirements of various aspects of material performance in practical applications. In view of the above problems in the prior art, the present invention provides a biomass polyester based on citronellol, a preparation method and use. On the one hand, the raw materials for preparing biomass polyesters come from biomass resources, so there is no need to worry about secondary pollution to the environment after the prepared polyester is used; on the other hand, the prepared biomass polyester is rich in a large amount of tea phenol, so that the polyester material can also ensure good viscosity in water. The polyester prepared using 4-methoxy-benzyl as an inhibitor has a large molecular weight, a high degree of polymerization, a high viscosity, and strong moisture resistance, and can be widely used in underwater adhesives and other fields. As mentioned above, a citronellol-based polyester prepared by the patent of the present invention will have a good market prospect.

[0048] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A biomass polyester P based on citronellol, characterized in that The structure is as follows: The value of X in the above structure is 50~110.

2. The preparation of a biomass polyester P based on citronellol according to claim 1, characterized in that The preparation comprises the following steps: (1) Synthesis of monomers Synthesis of a diol M1: At room temperature, citronellol with CAS No. 68916-43-8 is and hydrogen chloride in a certain proportion into a reaction vessel, stir to make it, then add an appropriate amount of Pd / CaCO3 solid particles, then heat the reaction mixture to 65-70°C, continue stirring and react for 2-4 hours, and then cool to room temperature. After filtering, add 0.10mol / L sodium hydroxide solution while stirring until the color of the solution does not change significantly, filter, extract the filtrate with carbon tetrachloride, take the lower layer of liquid after standing for a period of time, and then distill it at a temperature of about 85-90°C. The remaining liquid is the required diol monomer, and the structure is shown in Figure 2: Synthesis of a dibasic acid M2: Under low pressure, a certain proportion of 2-hydroxy-3,4-dimethoxybenzoic acid (CAS No. 5653-46-3) and chloroacetic acid are placed in a reactor, acetonitrile is added under stirring until the reactants are dissolved, and then 0.10 mol / L sodium hydroxide solution is added thereto, and the ratio of 0.10 mol / L sodium hydroxide solution to chloroacetic acid is 1:1.1-1.

2. The reaction mixture is then stirred and heated to 75-82°C. After reacting for 2-5 hours, the heating is stopped, and then cold water is added to the reaction mixture until the insoluble matter no longer increases. The reaction mixture is filtered, and the filter residue is washed with cold distilled water, filtered again, and the filter residue is dried in an oven at 60°C for 2-3 hours to obtain a dibasic acid monomer M2, the structure of which is shown in Formula 3: (2) The air in the reactor is replaced with nitrogen. Under nitrogen protection, the diol monomer M1, the dibasic acid monomer M2 and the polycondensation catalyst prepared in (1) are added into the reaction container in a certain proportion, and the reaction is stirred at 150-170°C for 5-6 hours. Then, the vacuum degree of the reaction system is controlled at 50-100 Pa. The reaction mixture is heated to 210-230°C within 1 hour. After the stirring reaction is continued for 3-4 hours, the reaction mixture is cooled to room temperature under a nitrogen atmosphere. Then, chloroform is added to the reaction mixture until it is dissolved, and filtered. Sufficient methanol is added to the filtrate until the precipitation no longer increases. Filter, wash the obtained filter residue with cold methanol for 3 times, filter again, and then dry it in an oven at 70-80°C for 2-3 hours to obtain a citronellol-based biomass polyester P.

3. The preparation of a biomass polyester P based on homovanillic acid according to claim 2, characterized in that: In step (1), the molar ratio of citronellol to hydrogen chloride is 1:(1.0-2.0); the molar ratio of 2-hydroxy-3,4-dimethoxybenzoic acid to chloroacetic acid is 1:(1.3-1.7).

4. The preparation of a biomass polyester P based on citronellol according to claim 2, characterized in that: The polycondensation catalyst in step (2) is a composite catalyst with one of TiCl4, TiCl3, and VOCl3 as a main catalyst and one of AlR2Cl, AlR3, RLi, and R2Mg as a co-catalyst, wherein R is a halogen atom. The amount of the polycondensation catalyst used is 0.01% of the mass of the dibasic acid monomer M2.

5. The preparation of a biomass polyester P based on homovanillic acid according to claim 2, characterized in that: In step (2), the molar ratio of the diol monomer M1 to the dibasic acid monomer M2 is 1:(1.0-1.2).

6. Use of the polyester P obtained by the method for preparing a biomass polyester P based on citronellol according to claims 2 to 5, characterized in that Used as an underwater adhesive for display, the preparation method of this adhesive is as follows: a biomass polyester P based on citronellol is reacted with a dopamine hydrochloride monomer at a mass ratio of 100: (80-85), and then an appropriate amount of DMSO is added, and the mixture is stirred and mixed evenly, an inhibitor (4-methoxy-benzaldehyde) is added to prevent free radical polymerization, argon gas is introduced to bubble, and the air in the liquid is removed, and the reaction is carried out at 65°C for 2.5 hours. The product is centrifuged at high speed, and a precipitant (8-hydroxyquinoline) is added after standing to remove impurities and monomer residues, and the residue is washed with propanol three times, and then the filter residue is dried in an oven at 60°C for 2-3 hours to obtain the target product.